(untitled) (Medical Forum Monthly, 2024)
Objectives: To access the morbidity and mortality of vaginal hysterectomy Study Design: Observational analytical study of cohort type Place and Duration of Study: Department of Obstetrics and Gynecology, Bolan Medical Complex Hospital, Quetta, from June 2008 to June 2010. Patients and Methods: This prospective study was conducted in department of Obstetrics and Gynecology Quetta from June 2008 to June 2010.One hundred twenty five patients undergone vaginal hysterectomy were studied. The age ranges from 25 -65years.Detailed history were taken. In each patient thorough systemic examination was performed and patient with finding of medical disorder were excluded. All analysis and computation including data base were done by SPSS 10. Results: During the study period, a total of one hundred twenty five women undergone vaginal hysterectomy were observed. All the cases were within age group ranging from 25-65 years of age. Out of them 48% were between 41 – 50 years, 27% between 51 -60 years, 9.6% belongs to 25-40 years of age and 15.2% were above the age of 60 years. Considering the commonest indication of vaginal hysterectomy is utero vaginal prolapsed, other important indications were dysfunctional uterine bleeding and uterine myoma. Comprises of the intra-operative and postoperative complications, show hemorrhage was the main complication during the surgery and it is the major cause of postoperative mortality in our study. Conclusion: Vaginal hysterectomy have less morbidity, shorter hospital stay and early resumption of patient to daily activities In our referral area where women’s delivered at there home attend by inexperienced DIAS- traditional birth attendants, rapid succession of pregnancy greatly enhance the Perineal tear leads to high ratio if utero vaginal prolapse. Vaginal hysterectomy having less morbidity and mortality, so it is more convenient in our center.